Three Notes on Science and Psychoanalysis - Tomšič, Samo (Filozofski vestnik, 2013)
The paper discusses the relation between psychoanalysis and science from the perspective of formalization and contingency. It departs from the role of biology in Freud, pointing out the insufficiency of his scientific preferences to account for the specific epistemological status of the unconscious and sexuality. Lacan’s notable reference to mathematical formalization then appears as a critical response to Freudian scientism. The paper in particular underlines the relation between formalization and contingency, which for Lacan was the central issue not only of psychoanalysis but also of modern science. This problem is addressed in reference to the polemic between the philosopher Émile Boutroux, who advocated the idea of the contingency of natural laws, and the mathematician Henri Poincaré, who decisively rejected Boutroux’s “speculations”. The paper then concludes with a brief outline of the main features of Lacan’s use of formalization, focusing especially on the “mathematization of the non-all” in which Lacan saw the point of encounter between scientific thinking and the real.